PEMBERDAYAAN UMKM BERBASIS DIGITAL MELALUI OPTIMALISASI GOOGLE MAPS DAN KONTEN PROMOSI MEDIA SOSIAL DI DESA DUKUH, INDRAMAYU - Dermawan, Windy; Renanta, Alifda Tisya; Dwi Damara, Zaskia Rahma; Rahma, Rizki Aulia; Zaman, Muhammad Badruz; Fitriyani, Syifa (Universitas Padjadjaran, 2026)
Low adoption of digital technology remains a challenge for Micro, Small, and Medium Enterprises (MSMEs) in rural areas, particularly regarding marketing and business visibility. This situation is evident among MSMEs in Dukuh Village, Indramayu Regency, where the majority have yet to utilize digital platforms to expand their market reach. This community service initiative aims to enhance the digital visibility of MSMEs by optimizing their presence on Google Maps and creating promotional content for social media. The methods employed included social mapping, MSME data collection, guidance on adding and optimizing business locations on Google Maps, and the creation of digital promotional content titled